Restructuring in SMEs in Europe - Mandl, Irene; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
Restructuring is a permanent feature of economic development in Europe, as companies must adapt to altered conditions in order to remain sustainable and competitive. At European and national level, governments and social partners have been debating and formulating policies on restructuring, aimed at providing adequate support for companies and their employees affected by restructuring. However, the policy focus to date has mainly been on large-scale restructuring, with restructuring in small and medium-sized enterprises (SMEs) receiving much less attention. Consequently, little is known about what motivates SMEs to change, the characteristics and outcomes of the restructuring processes, or about the factors that can foster or hinder their success. Given that SMEs represent more than 99% of European businesses and about two thirds of private sector employment, policymakers at all levels need to understand the characteristics and needs of the smaller firm in order to provide appropriate support for this backbone of the European economy.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Small business -- European Union countries; Small business -- Government policy -- European Union countries; Industrial restructuring -- European Union countries; Electronic books